Association Between Dietary Flavonoid Intake and Cardiovascular Health in Cancer Survivors: A Cross-Sectional Study - Li J; Chen G; Xie Z; Lin J; Luo S; Xu S (Journal of Multidisciplinary Healthcare)
Jing Li,1,2,* Ganxiao Chen,1,* Zhanxiong Xie,1 Jiayi Lin,1 Shunxiang Luo,1 Shanghua Xu1 1Department of Cardiology, Affiliated Nanping First Hospital, Fujian Medical University, Nanping, Fujian, People’s Republic of China; 2Key Laboratory of Gastrointestinal Cancer (Fujian Medical University), Ministry of Education, School of Basic Medical Sciences, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shanghua Xu; Shunxiang Luo, Department of Cardiology, Affiliated Nanping First Hospital of Fujian Medical University, Nanping, Fujian, People’s Republic of China, Email xushanghua@fjmu.edu.cn; luoshunxiang@fjmu.edu.cnPurpose: Flavonoids are naturally occurring compounds with diverse health-promoting properties. The purpose of this study was to explore the associations between dietary flavonoid intake and cardiovascular health in cancer survivors.Patients and Methods: We obtained data from the National Health and Nutrition Examination Survey (NHANES) 2007– 2008, 2009– 2010, and 2017– 2018 cycles. Weighted linear regression and restricted cubic spline (RCS) were used to explore the correlation between dietary flavonoid intake and cardiovascular health (Life’s Essential 8 (LE8) score) in cancer survivors. Then, weighted quantile sum (WQS) regression and quantile-based g-computation (qgcomp) models were performed to assess the mixed effects of the six flavonoid subclasses and to determine the major flavonoid types. Additionally, the protective effect of high flavonoid intake on cardiovascular health was further evaluated in different subgroups, and mediation analysis was used to explore mediating factors.Results: After adjusting for all covariates, compared to those in the first quartile, participants in the fourth quartile of total flavonoids, anthocyanidins, flavonols, flavanones, and flavones intake exhibited increases in LE8 scores of 3.24% (95% CI: 0.45– 6.03, P for trend=0.030), 6.25% (95% CI: 3.14– 9.36, P for trend< 0.001), 3.01% (95% CI: 1.33– 4.69, P for trend= 0.003), 3.23% (95% CI: 0.18– 6.27, P for trend=0.030), and 5.01% (95% CI: 2.42– 7.61, P for trend< 0.001), respectively. Meanwhile, significant non-linear relationships were supported by the RCS models. However, the weighted linear regression and RCS models did not reveal any clear correlations between isoflavone or flavan-3-ol intake and the LE8 score. Regarding mixed effects, anthocyanidin, flavonol, flavanone, and flavone intake were positively related to the LE8 score according to both the WQS and qgcomp models, and anthocyanidin intake was the major contributor.Conclusion: Our study indicated that dietary flavonoid intake is positively associated with cardiovascular health in cancer survivors, among which anthocyanidin intake might provide the most benefit. Keywords: weighted quantile sum, life’s essential 8 score, restricted cubic spline, NHANES